Geospatial Analysis of Land Use Land Cover Change Dynamics for Sustainable Urban Planning: A Case Study of Amaravati Region, Guntur, Andhra Pradesh, India - Yamala, Vinay Kumar; Ch, Madhulikha; Mokka, Jagannadha Rao (Iraqi Journal of Science, 2025)
Land use and land cover (LULC) are fundamental components of the Earth’s surface, representing the environment and influencing the lives of both human and natural communities, as well as their mutual interactions. Following the announcement of Amaravati as the capital city of the newly formed state of Andhra Pradesh, Land use and land cover (LULC) in the Amaravati region have undergone profound changes over the past decade, primarily due to anthropogenic activities resulting from urbanization. This study aims to identify and analyze general trends in Land Use/Land Cover Change (LULCC) that have occurred in the study area over a 12-year period, specifically from 2009 to 2021, using geospatial tools such as Remote Sensing and GIS techniques in the Amaravati region of Guntur, Andhra Pradesh, India. The study used multi-spectral satellite datasets for five years: Landsat 5-TM (2009) and Landsat 8-OLI (2015, 2017, 2019, and 2021). These images were pre-processed using Erdas Imagine 15, and five major LULC classes from Anderson’s classification Agriculture Land, Bare Land, Built-up Land, Vegetation, and Water Bodies were delineated by collecting spectral signatures and classified using the Maximum Likelihood method under the Supervised Image Classification Technique in the ArcGIS 10.5 platform. The study revealed that the percentage of agricultural lands decreased from 25.02% in 2009 to 44.08% in 2015 and then rose to 5.01% in 2021. Between 2009 and 2021, the percentage of built-up land increased from 5.12% to 11.70%. Throughout the study, vegetation covers steadily declined from 2009 to 2019 but started growing again in 2021. This results from abandoned land being used for urban development, which was subsequently reforested with open scrub. This had an impact on local farming methods. As a result, the spatiotemporal and prospective results of the LULC simulation could help policymakers examine changes in LULC intensity and the impact of socioeconomic factors, as well as support plans for sustainable urban development and environmental preservation of the city.